Temporal hemispheric dominance of omega-3: measurement of theta and delta brainwave using EEG / Nurul Aqilah Ariffin - Ariffin, Nurul Aqilah (2013)
Brainwave activities was said to differ under different conditions. The main objective of this study is to find the scientific proof on the effect of omega-3 in brain development as well as brainwave balancing index using EEG. There are four types of brainwave band which are Alpha, Beta, Delta and Theta. This study will only focus on Delta and Theta band wave. Twelve engineering students were selected as subjects for this study and each person was asked to consume omega-3 supplement. Brainwave activities were recorded through four stages of measurement using EEG and MATLAB software. Paired T-test analysis was used in order to find the correlation between the left and right brain before and after the consumption of omega-3. Based on the experiment, it shows that after a three month consumption of omega-3, delta brainwave was balanced but theta brainwave was unbalanced. However, the brain balancing index shows an improvement for both brainwaves.